Clinical experience and psychometric properties of the Cardiff Acne Disability Index (CADI). (1st October 2021) - Abdelrazik, Y.T.; Ali, F.M.; Salek, M.S.; Finlay, A.Y.
Summary: The Cardiff Acne Disability Index (CADI) is a questionnaire designed to measure the quality of life of teenagers and young adults with acne. It has been used clinically and within therapeutic research globally. This review aims to appraise all published data regarding the clinical and research experience of the CADI, its psychometric properties and validation, from its publication in 1992 until September 2020, in a single reference source. A literature search was conducted using MEDLINE via Ovid, PubMed, EBSCOhost, Web of Science and Scopus. All full articles in the English language were included. A total of 96 clinical studies were identified and analysed. The CADI has been used in 44 different countries, including four multinational studies, and has validated translations in 25 languages. Overall, 29 therapeutic interventions have used the CADI, demonstrating its responsiveness to change. The reliability of the CADI has been assessed in 14 studies through test–retest and internal consistency studies. In total, 57 studies have demonstrated aspects of its validity through correlation to other measures, and five studies have investigated the dimensionality of the CADI. There is evidence of high internal consistency, test–retest reliability, responsiveness to change and significant correlation with other objective measures. The minimal clinically important difference and validated score meaning bands have not yet been reported. This information is needed to improve the interpretability of CADI scores for clinical use and in research. The authors of the CADI have also rephrased Question 2 of the measure to ensure inclusivity.